2011
DOI: 10.1016/j.gca.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of hot springs along the Eastern Lau Spreading Center

Abstract: The Eastern Lau Spreading Center (ELSC) is the southernmost part of the back-arc spreading axis in the Lau Basin, west of the Tonga trench and the active Tofua volcanic arc.Over its 397-km length it exhibits large and systematic changes in spreading rate, magmatic/tectonic processes, and proximity to the volcanic arc. In 2005 we collected 81 samples of vent water from six hydrothermal fields along the ELSC. The chemistry of these waters varies both within and between vent fields, in response to changes in subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 59 publications
6
95
0
1
Order By: Relevance
“…concentration and bioenergetic potential of sulfur in the water column overprints the geochemical differences in host rocks and end-member hydrothermal fluid chemistry along the ELSC (Mottl et al, 2011), which have been found to influence microbial diversity on the seafloor (Flores et al, 2012;Sylvan et al 2013). These results are consistent with a gene-centric mathematical model of the Abe vent at ELSC, which shows that sulfur metabolisms dominate and that seafloor populations were rapidly diluted out of the rising plume (Reed et al, 2015) and also with more extensive analysis of ELSC plumes, showing that differences in community composition between vent fields are not significant (Sheik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…concentration and bioenergetic potential of sulfur in the water column overprints the geochemical differences in host rocks and end-member hydrothermal fluid chemistry along the ELSC (Mottl et al, 2011), which have been found to influence microbial diversity on the seafloor (Flores et al, 2012;Sylvan et al 2013). These results are consistent with a gene-centric mathematical model of the Abe vent at ELSC, which shows that sulfur metabolisms dominate and that seafloor populations were rapidly diluted out of the rising plume (Reed et al, 2015) and also with more extensive analysis of ELSC plumes, showing that differences in community composition between vent fields are not significant (Sheik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Bioenergetic and thermodynamic modeling Equilibrium thermodynamic reaction path modeling was used to predict mineral precipitation, chemical concentrations and activity coefficients resulting from the mixing of sea water with end-member fluid from the hydrothermal vents (Mottl et al, 2011). Supplementary Table S2 lists the end-member fluid concentrations utilized in our model.…”
Section: Functional Gene Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At some unusual vent sites in this region, where smoker chimneys are distinctly reddish brown, snails and mussels are notably absent, replaced by low densities of shrimps, crabs, polynoid polychaetes, and limpets. This faunal anomaly may be in response to high metal concentrations (Mottl et al, 2011). On the northern MAR, vent communities along a 3,000 km section between 11 and 38 • N differ markedly in species composition, in patterns that correspond to both depth and fluid chemistry (Desbruyères et al, 2000).…”
Section: Local Controls Of Environment and Species Interactionsmentioning
confidence: 99%
“…The availability and nature of reduced compounds will influence the autotrophic base of the food chain while fluid character will affect habitat suitability. Regional community diversity should be affected because of the high within-region variability in fluids and magma supply (e.g., Mottl et al, 2011); however, evidence is accumulating slowly due to limited fieldwork. For example, chronic eruptive activity on NW Rota (Mariana Arc) results in a very limited vent community of a few wide-dispersing species (Embley et al, 2006), while other volcanoes in the arc foster communities that differ from site to site due to dominant fluid and substratum characteristics Stevens et al, 2015).…”
Section: Dispersal Effects On Regional Species Diversitymentioning
confidence: 99%